Analysis of the Development of the Village Development Index (IDM) Status in Coastal Villages in Kuala Kampar District, 2021–2024 - Syakirah Athiyyah; Taryono Taryono; Naila Septa Ridhoni; Melani Noviantori Ramadhan; Della Novita Sari; Klara Marsyakila; Aprillina Aprillina (Universitas Dharmawangsa Medan, 2025)
This study aims to analyze the development of the Village Development Index in coastal villages in Kuala Kampar District during the period 2021–2024. This study uses a quantitative descriptive method with a time series approach to observe trends in IDM value changes and the contribution of each dimension, namely social resilience, economic resilience, and environmental resilience. The data used is secondary data obtained from the official website of the Ministry of Villages, Disadvantaged Regions, and Transmigration. The results of the study show a significant increase in collective status, where six of the nine villages successfully transitioned from “Advanced” to “Independent” status during the observation period. The most striking change occurred in 2023, along with a sharp increase in the average IDM score. Of the three dimensions, environmental resilience recorded the highest index value, while economic resilience experienced the most dynamic increase, becoming the main driver of village status change. These findings indicate that economic diversification and good environmental management play an important role in accelerating coastal village development.